Smoking and trimalleolar fractures are risk factors for infection after open reduction and internal fixation of closed ankle fractures: A multicenter retrospective study of 1, 201 fractures. Issue 7 (July 2021) - Sato, Toshifumi; Takegami, Yasuhiko; Sugino, Takayuki; Bando, Kosuke; Fujita, Tomoki; Imagama, Shiro
Highlights: This multicenter retrospective study showed a 5.7% (69/1201 patients) of wound infection after surgery for ankle fracture. Staphylococcus was the most frequent causative organism. Smoking and trimalleolar fracture were significant risk factors for infection. Abstract: Introduction: One of the complications of the surgical therapy for ankle fractures includes wound infection. This study aimed to evaluate postoperative function and clarify the risk factors associated with postoperative wound infection in patients receiving the open reduction and internal fixation for ankle fracture through a multicenter study. Subjects and method: Among 1421 patients diagnosed as having closed ankle fracture and who were treated by surgical therapy in 11 institutions from 2014 through 2019, 1201 patients (men, n = 512, women, n = 689; the mean (SD) age, 50.9 (15.6) years; the mean body mass index [BMI] (SD), 24.3 (4.2) kg/m2) were included as subjects. Excluded were 220 patients due to self-termination of treatment, inability to follow up after discharge, open fracture, distal tibia shaft fracture, and pilon fracture. We extracted the following as risk factors of wound infection: age, sex, BMI, fracture type, injury energy and histories of smoking, diabetes, arteriosclerosis, heart failure and myocardial infarction. We conducted logistic regression analysis to investigate the risk factors of wound infection using these extracted items as explanatory variables and the presence or absence of wound infection as the response variable. Results: Wound infection occurred after surgery for closed ankle fracture in 69 the 1201 patients (5.7%). The causative organism was methicillin-susceptible Staphylococcus aureus (MSSA) in 15 patients, methicillin-resistant S. aureus (MRSA) in 4 patients, Finegoldia magna in one patient, and S. haemolyticus in one patient. In the other patients, causative organisms were not detected, culture of the causative organisms was not conducted, or they were unknown. The univariate analysis showed significant differences in sex (p = 0.01) and for smoking (p = 0.002), fracture type (p = 0.02) and heart failure (p = 0.042). Logistic regression analysis showed that smoking and type of fracture (trimalleolar fracture) were significant explanatory factors for infection (odds ratio 1.83 and 1.98, p = 0 .040 and 0.042, respectively). Conclusions: At 5.7%, the rate of postoperative wound infection in closed ankle fracture was not low. Staphylococcus was the most frequent causative organism. The surgeon should pay attention infection after surgery in the patients who had a trimalleolar fracture or smoking habits.